The Role of Customer Satisfaction in Mediating the Effect of Store Atmosphere and Emotional Branding on Customer Loyalty - Viona Ramadani; Aang Curatman (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of store atmosphere and emotional branding on customer loyalty with consumer satisfaction as a mediating variable among Generation Z consumers of Kopi Kenangan in Cirebon. The study uses a quantitative approach with a causal associative design. The research sample consisted of 230 Generation Z respondents selected through purposive sampling. Data were collected using a Likert scale questionnaire and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method using the SmartPLS application. The results showed that emotional branding and customer satisfaction had a positive and significant effect on customer loyalty. Store atmosphere had a positive and significant effect on customer satisfaction but did not have a significant direct effect on customer loyalty. Customer satisfaction was found to fully mediate the effect of store atmosphere on customer loyalty and partially mediate the effect of emotional branding on customer loyalty. These findings confirm that Generation Z consumer loyalty is more influenced by emotional experiences and satisfaction levels than by physical store factors directly.